2021
DOI: 10.1038/s41598-021-85162-0
|View full text |Cite
|
Sign up to set email alerts
|

Apelin promotes blood and lymph vessel formation and the growth of melanoma lung metastasis

Abstract: Apelin, a ligand of the APJ receptor, is overexpressed in several human cancers and plays an important role in tumor angiogenesis and growth in various experimental systems. We investigated the role of apelin signaling in the malignant behavior of cutaneous melanoma. Murine B16 and human A375 melanoma cell lines were stably transfected with apelin encoding or control vectors. Apelin overexpression significantly increased melanoma cell migration and invasion in vitro, but it had no impact on its proliferation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…A growing body of evidence shows that the therapeutic efficacy of MSCs in MI is largely attributed to their paracrine effects, especially their angiogenic capacity. Interestingly, Apelin mediates cellular angiogenesis via multiple pathways [ 43 , 44 ]. We also found that Apelin-13 pretreatment greatly enhanced the angiogenic capacity of MSCs, as evidenced by the increased capillary-like tube formation of HUVECs cultured with conditioned medium and enhanced capillary and arteriole density in the ischemic heart tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence shows that the therapeutic efficacy of MSCs in MI is largely attributed to their paracrine effects, especially their angiogenic capacity. Interestingly, Apelin mediates cellular angiogenesis via multiple pathways [ 43 , 44 ]. We also found that Apelin-13 pretreatment greatly enhanced the angiogenic capacity of MSCs, as evidenced by the increased capillary-like tube formation of HUVECs cultured with conditioned medium and enhanced capillary and arteriole density in the ischemic heart tissue.…”
Section: Discussionmentioning
confidence: 99%
“…As a new lymphangiogenesis factor, apelin may have potential clinical research value for a new type of antitumor therapy targeting lymphangiogenesis (Berta et al, 2014). Apelin can promote the lymph vascularization of skin melanoma and the growth of lung metastases (Berta et al, 2021). High apelin levels can be used as a diagnostic indicator for MM, which has excellent clinical diagnostic value for MM (Maden et al, 2016).…”
Section: Role Of Apelin/apj System In Cancer Development and Progressionmentioning
confidence: 99%
“…Next, research revealed that, also, apelin overexpression increased the number and size of melanoma lung metastases in mice. Additionally, in vitro studies showed that higher apelin expression enhances the migratory and invasive abilities of melanoma cell lines, but does not influence their proliferation [132]. However, the inhibition of miR-4286 altered the mRNA expression of, among others, this hormone gene that next was implicated in the regulation of melanoma cell proliferation and apoptosis [200].…”
Section: Apelinmentioning
confidence: 99%
“…However, the inhibition of miR-4286 altered the mRNA expression of, among others, this hormone gene that next was implicated in the regulation of melanoma cell proliferation and apoptosis [200]. Interestingly, apelin and VEGF plasma concentrations were more elevated in patients with melanoma than in healthy individuals [132].…”
Section: Apelinmentioning
confidence: 99%